Corporate Governance: Company and Country Competitiveness - Boeva, Bistra (Research Papers, 2012)
The transition from a planned to a market economy is mainly about dismantling long-term structures and mechanisms and building (and rebuilding) new institutions from scratch. Corporate Governance is an integral part of these new institutions. The focus of this research is to investigate the role of corporate governance from a different perspective: the objective is not about what corporate governance is in a new market economy, but rather to trace the contribution corporate governance makes to company and country competitiveness. Special attention is paid to the developments of Corporate Governance in Bulgarian companies since 2007 – the start of Bulgaria’s EU membership The basis of this paper is formed by the results of a research project (2009-2011).In this paper corporate governance is regarded as a set of relationships between shareowners, directors and managers on one hand , and the stakeholders on the other that contributes to company growth and its sustainable development. More specifically Corporate governance is accepted as a set of rules that some listed companies in Bulgaria implement on a voluntary principle (National Code for Corporate Governance, 2007 – soft law) and the majority of the other companies listed on the Bulgarian Stock Exchange understand the importance of corporate governance as a set of rules that the stock exchange and the state imposed on a top-down principle (hard law).With regard to the preliminary research and the objective of the project a few hypotheses were determined and more specifically that corporate governance is an established practice, which impacts a company’s competitiveness. The research is conducted via a set of methods that meet the concept of triangulation: literature survey, international statistics and field studies.It is noteworthy to point out that the literature observation revealed only a limited number of studies on the relationship between corporate governance and company competitiveness (strategic management school; neo-institutional economics). At the same time the majority of authors on this subject are inclined to investigate the contribution of corporate governance to economic performance or, to put it another way, the point of view of most scholars is the perspective of the finance and capital markets etc.The information extracted from the annual reports released on the Global Competitiveness Index by the World Economic Forum; the annual reports of Institute for Management Development (World Competitiveness Yearbook) and the annual reports of World Bank (Doing Business) suggests evidence that corporate governance is among the key driving forces that shape competitiveness on macro and micro levels. These reports indicate that the level of Corporate Governance in Bulgarian companies differs in terms of separate elements of Corporate Governance principles. While disclosure, transparency and investor protection are at a good level, the capacity or efficacy of the board members is at a low level, which fails to add value to the competitiveness of both company and country.In the course of the field research these results are investigated from the perspective of the board members of listed Bulgarian companies. The purpose of this particular field search is to establish the attitudes of board members towards the results released by the WEF. It is noteworthy to point that the sample included listed (100) companies with one and two tier systems of governance. The type of ownership – dispersed or concentrated, was not under survey. The majority of companies declared that they comply with the National Corporate Governance Code. The crossdata processing attempted to reveal not only the attitudes of corporate boards members, but the relationship between the learning curve and the opinion of the respondents. Again, it is noteworthy to point out that the longer serving members accept the negative evaluation. This suggests that the learning curve determines the attitude towards the WEF evaluation. The analysis of the data also revealed another interesting trend: The majority of the independent board members did not accept the evaluation. Contrary to that, the representatives of the shareholders accepted the above evaluation, whereas the representatives of the major shareholders are divided equally cornering the correctness of the evaluation. It would not be fair from a scientific point of view to draw final conclusions, but is clear that the responses of the independent directors do not correspond to a reasonable understanding about their role in the corporate boards.The project and the paper suggest evidence (theoretical and empirical) that prove the view that corporate governance is among the key drives of company competitiveness. The above assumption should be interpreted from various perspectives: for a country that has only recently joined the global market economy and is strongly exposed to the positive and negative trends within the EU and the global economy it is important to stick to well established rules and institutions. For the business community it is important to underline those institutions matters within the international and global competition. And finally another important conclusion is that there is still a theoretical vacuum concerning the role of Corporate Governance for the competitiveness of the company and the new venue for academia research is discovered.